STUDY OF POSSIBILITY OF APPLICATION OF COLD-HARDENING MIXTURES WITH DIFFERENT GUMS IN CONDITIONS OF FGUP “URALVAGONZAVOD - V. E. Kuznetsov; L. P. Evdokimova; T. A. Popova; E. M. Bocharnikova (Литьë и металлургия, 2004)
The possibilities of application of cold-hardening mixtures with different gums in conditions of Uralvagonzavod are examined.